Freedom Deprivation Punishment in Serbia during 1804-1860 - Mirković, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
This text is on freedom deprivation punishment in Serbia during the first half of 19th century, i.e. since the beginning of the First Serbian uprising in 1804 and till passing the Criminal law in 1860. Author first emphasises that the freedom deprivation punishment doesn’t have long tradition, although in medieval Serbia and under Turkish rule existed imprisonment in dungeon, but it was foremost some form of custody before a trial, and subsequently as keeping a prisoner after the verdict until its effectuation. It wasn’t a freedom deprivation punishment in modern sense. During 1804 – 1813 there was so called “haps” i.e. apprehension, though Uprising authorities built also “real” prisons for punishment purpose. Imprisonment of culprits was a condition for compulsory labour, which could be very useful utilized under given circumstances.          Since the beginning 1820-ties when first Serbian courts were established, beside “haps” appears also imprisonment in heavy shackles. However there was no substantial difference between apprehension and imprisonment. In this time the sentence to imprisonment was combined with the punishment with beating (or sometimes with the flogging at the end of imprisonment). The Regulation of County courts from January 26th 1840 mentions several forms of freedom deprivation punishment, but in praxis freedom deprivation was reduced on either “eternal” imprisonment or time-sentenced imprisonment.            Since the beginning of 1840-ties freedom deprivation was more frequently used as punishment and its implementation was continually spreading. For heaviest crimes was instead death penalty and running gauntlet sentenced freedom deprivation, either from courts or from supreme authority in the amnesty process.          Imprisonment was effectuated either at police reformatories (for shorter penalties) or at the penitentiary institutions (for longer imprisonment). By the end of 1830-ties an issue of imprisonment of female perpetrators emerged, together with the problem of freedom deprivation punishment for mentally ill committers of criminal acts.            Relatively early and in increasing number appeared regulations on effectuation of freedom deprivation punishments, intended to solve numerous practical and principle questions about realisation of this penalty. Finally on December 20th 1851 was issued the Structure of Experimental Economy in Topčider Penitentiary, which regulated treatment of convicts, their work, penalties, behaviour of guards etc. A new punishment purpose has become noticeable – compulsory re-education and remission through work, as a difference to previous aims: sheer intimidation and neutralization of public danger.            At the end of herein observed time, in the year 1858 appeared first theoretical work on penitentiary institutions and Project of Law on Effectuation of Freedom Deprivation Penalties. This project was elaborated on broad fundaments, with regulations for each form of freedom deprivation penalty, but wasn’t accepted due to the lack of financial means.